(untitled) (International Journal of Engineering and Computer Science, 2018)
Delay tolerant networks (DTNs) may lack continuous network connectivity. Routing is thus challenging since it must handle network partitioning, long delays, and dynamic topology and limited power sources in such networks. Social Group-Based routing is an optimal routing, the protocol maximize data delivery while minimizing network overhead and packet delay by efficiently spreading the packet copies in the network. Social grouping concept is used for routing effectively by selecting minimum hop path from the all possible path of tree contacts. The members of its own group should be known to all and message is forwarded to member of other social group only. Messages to the nearest group is forwarded without waiting for the other group member, by selecting most suitable relay node from the same group. The fuzzification of degree of connectivity that strengthen by frequent meeting of nodes and the mobility of nodes help to fuzzify the membership of nodes in the case of overlapping communities to select the better relay node. The protocol achieves higher delivery ratio, less network overhead and less average delay compared to other routing protocols